A multivariate planning model - city structure : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Statistics. - Crawford, Peter (Massey University, 1972)
The genesis of this study is post graduate research in Urban Geography at Canterbury University in 1966. At that time a crude multivariate Centroid model of 95 New Zealand towns and cities was constructed. Based upon 60 socio-economic variables two factors for each of the years 1951, 1956 and 1961 were extracted and compared. The present study, which is a considerable refinement upon the earlier research, incorporates not only tremendous advancement in multivariate design methodology and application, but also parallel advancements that have been made in computing facilities over the last five years. The objective of this research is to construct a multivariate statistical planning model that is both statistically precise and meaningful in its application. Particular emphasis is placed upon the need to organise in a systematic and meaningful manner the increasingly greater variety of statistics that portray urban growth. Stress is placed upon the utility of the multivariate technique as a tool in the author's profession of Town Planning. [From Preface]
Keywords: City planning; Mathematical models; Multivariate analysis